2013
DOI: 10.1016/j.chembiol.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

N-Carbamoylation of 2,4-Diaminobutyrate Reroutes the Outcome in Padanamide Biosynthesis

Abstract: Padanamides are linear tetrapeptides notable for the absence of proteinogenic amino acids in their structures. In particular, two unusual heterocycles, (S)-3-amino-2-oxopyrrolidine-1-carboxamide (S-Aopc) and (S)-3-aminopiperidine-2,6-dione (S-Apd), are found at the C-termini of padanamides A and B, respectively. Here we identify the padanamide biosynthetic gene cluster and carry out systematic gene inactivation studies. Our results show that padanamides are synthesized by highly dissociated hybrid nonribosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…Apart from the high affinity of EnuR for N-(a)-ADABA, this compound has the additional advantage of being a specific ectoine-derived metabolite (Fig. 1), whereas DABA occurs also as an intermediate in other metabolic and biosynthetic processes in microorganisms (Ikai and Yamamoto, 1997;Du et al, 2013;Fidalgo et al, 2016), including the biosynthesis of ectoine (Ono et al, 1999) (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the high affinity of EnuR for N-(a)-ADABA, this compound has the additional advantage of being a specific ectoine-derived metabolite (Fig. 1), whereas DABA occurs also as an intermediate in other metabolic and biosynthetic processes in microorganisms (Ikai and Yamamoto, 1997;Du et al, 2013;Fidalgo et al, 2016), including the biosynthesis of ectoine (Ono et al, 1999) (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Since DABA is also produced in microbial pathways not involved in ectoine catabolism (Ikai and Yamamoto, 1997;Du et al, 2013;Fidalgo et al, 2016), we set out to genetically and biochemically define the physiologically most relevant system-specific inducer for EnuR. We identify it here as N-(a)-ADABA, a highly specific intermediate of ectoine catabolism (Schwibbert et al, 2011;Schulz et al, 2017) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the structures of DPTCase, DBTCase and UGTCase have not yet been determined, their models can be reliably built based on the structures of OTCase and ATCase because of their sequence similarity. These structural models suggest that the D250 residue within the HDLP motif ( Saccharothrix mutabilis DPTCase numbering), which is a characteristic feature in DPTCase and DBTCase sequences [ 70 ], will likely interact with the α-amino group of the second substrate and residue R212 from the equivalent 240’s loop may be involved in anchoring the carboxyl group of that substrate. In a similar way, T298 from the characteristic H(T/S)LP motif of UGTCase ( Rubrobacter xylanophilus UGTCase numbering) [ 31 ] is likely to form a hydrogen bond with the ureido N atom of ureidoglycine.…”
Section: Active Site and Substrate Specificitiesmentioning
confidence: 99%
“…After separating the similar compounds from the two species we focused our efforts on S. bangulaensis , which produced significantly higher levels of an identical suite of active compounds. Further analysis revealed that the major metabolite was the recently described actinoramide A ( 1 ) /padanamide A 15,16 , whose biosynthetic pathway has recently been characterized 17 . Actinoramide B ( 2 ), also isolated among the active components, was identified by comparison with published spectroscopic data ( 1 H and 13 C NMR, HRMS, specific rotation).…”
Section: Resultsmentioning
confidence: 99%